KEMAMPUAN MANAJERIAL PIMPINAN PONDOK PESANTREN DALAM PENGELOLAAN SUMBER DAYA MANUSIA - ., Suarga (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Islamic boarding school is an institution that can not be separated from the phenomenon of cooperation, considering the boarding school is a manifestation of the ideals or desire to create a successor cadre or santri who are experts in the field of science, especially religious knowledge. Pesantren also must realize the ability to develop and practice the religious knowledge in the midst of society. Noble ideals or desires are difficult to be realized if only done by a kiai or caregiver, because human nature does have limitations, so it takes the involvement of various humans through the process of cooperation in realizing these ideals or desires. The dynamics of pesantren development when juxtaposed with educational institutions that once appeared in Indonesia, is the oldest system of education today and is considered an indigenous Indonesian product. This education was originally an Islamic religious education that started since the emergence of Islamic society.